ANTIOXIDANT AND ANTIMICROBIAL ACTIVITIES OF AN ETHNOBOTANICALLY IMPORTANT PLANT NOTHOLIRION THOMSONIANUM FROM DISTRICT KOTLI, AZAD JAMMU & KASHMIR - M. Ajaib; S. Ali; Z. Khan (Journal of Animal and Plant Sciences, 2014)
The petroleum ether, chloroform, methanol and aqueous extracts of Notholirion thomsonianum (D. Don) Stapf, obtained by maceration method were tested for their antioxidant potential, antibacterial and antifungal activities. Antioxidant activity was checked by four methods: 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) scavenging activity, total antioxidant activity, ferric reducing antioxidant power (FRAP) assay and ferric thiocyanate (FTC) assay along with the determination of their total phenolic contents. The results revealed that among these fractions the methanol soluble fraction showed highest DPPH radical scavenging activity, i.e. 91.26±0.44% inhibition of DPPH radical at a concentration of 500 µg/ml with IC50 value 22.08±0.69 relative to butylated hydroxytoluene (BHT), having IC50 of 12.52 ± 0.89 μg/ml. Chloroform extract showed highest total antioxidant activity, i.e. 0.730±10.56 as well as highest FRAP value, i.e. 22.66±1.33 TE µM/ml of aqueous extract. Methanol, chloroform and petroleum ether extracts showed considerable amounts of total phenolic contents, i.e. 147±0.59 and 145±0.85 and 141.83±2.36 GAE mg/g respectively. Methanol extract showed good value of inhibition of lipid peroxidation, i.e. 47.19±1.25. Antimicrobial activity was evaluated by well diffusion method against some bacteria and fungi. The highest zone of inhibition was formed by aqueous extract, i.e. 35±1.31 against E. coli followed 32±0.32 and 32±0.9 of aqueous extract against Streptococcus faecelis and Staphylococcus aureus respectively. The highest antifungal zone of inhibition was formed by aqueous and petroleum ether extract, i.e. 40±1.1 and 37±1.73 against Aspergillus oryzaeand Aspergillus niger respectively.The Minimum Inhibitory Concentration (MIC) results revealed that the methanolic extract 0.009 μg/ml showed more resistance against Pseudomonas aeruginosa.
Keywords: Notholirion thomsonianum; DPPH assay; total antioxidant activity; FRAP value; Inhibition of lipid peroxidation (%); antimicrobial; MIC